Empirical Analysis of the Tourism-Terrorism Nexus: The Nigerian Experience (2017)
This paper examined the relationship among tourism, terrorism and broad economic aggregates. We made use of the impulse response and variance decomposition of the Vector Autoregression (VAR) on the Nigerian economy from 1995Q1 to 2012Q4. Besides the appropriate unit root and cointegration properties of the variables, the result revealed, that terrorism had negative effects on other variables of the study, especially tourism. Also, shocks in other variables are majorly caused by terrorism. The study also revealed that tourism responds positively to FDI, but its response to GDP and FDI are mixed overtime. Therefore, growth-promoting and other complimentary policies that will engender aggregate welfare improvement need to be pursued to ensure that the tourism sector sidestep the adverse consequences of terrorism.